Homozygosity mapping in patients with cone-rod dystrophy: novel mutations and clinical characterizations - Littink, Karin; Koenekoop, Robert K.; van den Born, L. Ingeborgh; Collin, Rob W. J.; Moruz, Luminita; Veltman, Joris A.; Roosing, Susanne; Zonneveld, Marijke N.; Omar, Amer; Darvish, Mahshad; Lopez, Irma; Kroes, Hester Y.; et al. (Investigative ophthalmology & visual science, 2010)
To determine the genetic defect and to describe the clinical characteristics in a cohort of mainly nonconsanguineous cone-rod dystrophy (CRD) patients.
Gesehen am 28.03.2023